Population-level effects of the national diabetes prevention programme (FIN-D2D) on the body weight, the waist circumference, and the prevalence of obesity - Ebeling Tapani; Vanhala Mauno; Puolijoki Hannu; Oksa Heikki; Saaristo Timo; Salopuro Titta M; Niskanen Leo; Tuomilehto Jaakko; Uusitupa Matti; Peltonen Markku (BMC, 2011)
Abstract Background The implementation project of the national diabetes prevention programme in Finland, FIN-D2D, was carried out in primary health care in the area of five hospital districts during 2003-2007. Methods The population strategy of FIN-D2D was primarily aimed at increasing the awareness of type 2 diabetes and preventing obesity. To investigate the effects of this strategy, we studied the changes in the prevalence of obesity, overweight, and central obesity among a random independent sample of individuals aged 45-74 years in the FIN-D2D area; and assessed whether they differed from a sample of individuals in the control area, which consisted of four geographical areas not participating in FIN-D2D (FINRISK study). Data was obtained for 5850/ 6406 (in the beginning/ in the end) individuals. The duration of the observation period varied from three to five years. Results The mean body weight decreased from 78.7 to 78.1 kg (p = 0.041) in the FIN-D2D area, and from 78.7 to 78.0 kg (p = NS) in the control area. The prevalence of obesity (BMI ≥30 kg/m2) decreased in the FIN-D2D area (26.5% vs. 24.4%, p = 0.015), and in the control area (28.4% vs. 25.2%, p = 0.005). The prevalence of morbid obesity (BMI ≥40 kg/m2) remained unchanged in the FIN-D2D area, but increased in the control area (1.2% vs. 2.3%, p = 0.007). The mean waist circumference remained unchanged in the FIN-D2D area, but increased in the control area (92.8 vs. 94.0 cm, p = 0.005). Conclusions The prevalence of obesity may be decreasing among 45-74 year old Finns. We still need a longer time perspective and future studies to see whether this favourable trend can be sustained in Finland. The actions of this implementation project can at least partly explain the differences in the mean waist circumference and the prevalence of morbid obesity between the intervention and control areas.